Topiramate is more effective than acetazolamide at lowering intracranial pressure. (February 2019) - Scotton, William J; Botfield, Hannah F; Westgate, Connar SJ; Mitchell, James L; Yiangou, Andreas; Uldall, Maria S; Jensen, Rigmor H; Sinclair, Alex J
Background: The management of idiopathic intracranial hypertension focuses on reducing intracranial pressure to preserve vision and reduce headaches. There is sparse evidence to support the use of some of the drugs commonly used to manage idiopathic intracranial hypertension, therefore we propose to evaluate the efficacy of these drugs at lowering intracranial pressure in healthy rats. Methods: We measured intracranial pressure in female rats before and after subcutaneous administration of acetazolamide, topiramate, furosemide, amiloride and octreotide at clinical doses (equivalent to a single human dose) and high doses (equivalent to a human daily dose). In addition, we measured intracranial pressure after oral administration of acetazolamide and topiramate. Results: At clinical and high doses, subcutaneous administration of topiramate lowered intracranial pressure by 32% ( p  = 0.0009) and 21% ( p  = 0.015) respectively. There was no significant reduction in intracranial pressure noted with acetazolamide, furosemide, amiloride or octreotide at any dose. Oral administration of topiramate significantly lowered intracranial pressure by 22% ( p  = 0.018), compared to 5% reduction with acetazolamide ( p  = >0.999). Conclusion: Our in vivo studies demonstrated that both subcutaneous and oral administration of topiramate significantly lowers intracranial pressure. Other drugs tested, including acetazolamide, did not significantly reduce intracranial pressure. Future clinical trials evaluating the efficacy and side effects of topiramate in idiopathic intracranial hypertension patients would be of interest.